A renewed focus on primary health care: revitalize or reframe? - Rifkin Susan; Bhatia Mrigesh (BMC, 2010)
Abstract The year 2008 celebrated 30 years of Primary Health Care (PHC) policy emerging from the Alma Ata Declaration with publication of two key reports, the World Health Report 2008 and the Report of the Commission on the Social Determinants of Health. Both reports reaffirmed the relevance of PHC in terms of its vision and values in today's world. However, important challenges in terms of defining PHC, equity and empowerment need to be addressed. This article takes the form of a commentary reviewing developments in the last 30 years and discusses the future of this policy. Three challenges are put forward for discussion (i) the challenge of moving away from a narrow technical bio-medical paradigm of health to a broader social determinants approach and the need to differentiate primary care from primary health care; (ii) The challenge of tackling the equity implications of the market oriented reforms and ensuring that the role of the State in the provision of welfare services is not further weakened; and (iii) the challenge of finding ways to develop local community commitments especially in terms of empowerment. These challenges need to be addressed if PHC is to remain relevant in today's context. The paper concludes that it is not sufficient to revitalize PHC of the Alma Ata Declaration but it must be reframed in light of the above discussion.